Standardization of surgical treatment of acute electrical trauma - Edmar Maciel Lima Junior; Victor Monteiro Maciel Lima; Ezequiel Aguiar Parente; Guilherme Emilio Ferreira (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Electrical burns are responsible for 5% to 15% of cases of burn accidents. The majority is associated with workplace accidents, in which high-voltage injuries (>1,000 V) predominate in male patients. The mortality rates vary from 2% to 15% in different burn centers. The objective is to review the standardization of surgical steps in the acute phase of debridement (the first 15 days) by comparison of creatine phosphokinase levels, intravenous hydration, and photographs to implement routine surgical stages. METHODS: This was a quantitative, prospective study performed in a public hospital in the city of Fortaleza, Brazil, between July 2013 and December 2015. The population was composed of young adults between 15 and 50 years, of both sexes, who experienced electrical burns, with third-degree injuries and muscle involvement. RESULTS: Of the 15 patients in the study, 9 (60%) patients underwent 13 surgical amputation procedures and 6 (40%) patients did not undergo amputation. One patient underwent three amputation procedures in the same limb (toe, foot, and thigh) and another patient underwent two amputations in the upper limbs. CONCLUSION: Treatment in the acute phase of electrical shock must include immediate and adequate intravenous fluid replacement, along with surgical procedures of debridement and amputations, as early as possible, in steps with intervals of 48 to 72 hours.